Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2196/23006
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward the Use of Voice-Assisted Technologies Among People With Parkinson Disease: Findings From a Web-Based Survey

Abstract: Background Speech problems are common in people living with Parkinson disease (PD), limiting communication and ultimately affecting their quality of life. Voice-assisted technology in health and care settings has shown some potential in small-scale studies to address such problems, with a retrospective analysis of user reviews reporting anecdotal communication effects and promising usability features when using this technology for people with a range of disabilities. However, there is a need for re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…They highlighted the positive impacts of having a device that would provide such a source of feedback on speech production; if the device could understand a client, they were given clarification that they were speaking intelligibly. This echoes the findings of other studies, which have highlighted the successful experiences of users with speech impairment when using commercial VAT devices [ 27 , 28 , 32 ]. As highlighted by our professional SLT participants, the ability to practice speech at home and obtain real-time, impartial feedback from the devices was found to improve word production accuracy and increase clients' motivation to perform home therapy practice, both of which are SLT outcomes that might regularly be targeted in formal therapy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…They highlighted the positive impacts of having a device that would provide such a source of feedback on speech production; if the device could understand a client, they were given clarification that they were speaking intelligibly. This echoes the findings of other studies, which have highlighted the successful experiences of users with speech impairment when using commercial VAT devices [ 27 , 28 , 32 ]. As highlighted by our professional SLT participants, the ability to practice speech at home and obtain real-time, impartial feedback from the devices was found to improve word production accuracy and increase clients' motivation to perform home therapy practice, both of which are SLT outcomes that might regularly be targeted in formal therapy.…”
Section: Discussionsupporting
confidence: 87%
“…A study [ 27 ] also reported similar findings, discussing that some Alexa users self-reported speech improvements, with a need for distinct pronunciation when using the device actively improving users’ speech through continuous practice. Duffy et al [ 32 ] also found self-reported speech improvements in approximately 25% of people with Parkinson disease who were using VATs but did not delve into why participants felt this might be happening. This is an exciting and ripe area for future research, which might explore the extent to which speech changes actually occur through device use, how they are maintained, and how speech outcomes being achieved through device use might be measured in SLT practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it is currently unclear how information collected from voice-based technologies can be transmitted and incorporated into existing electronic medical record systems while ensuring regulatory compliance. In studies exploring patient concerns, only a minority (~10%) reported any significant concerns regarding privacy or confidentiality [ 48 •]. In surveys of both users and nonusers of voice-based technologies, we see that users have much lower concerns regarding security, suggesting that perceptions of security and privacy may prevent the widespread adoption of voice technologies in the general population [ 49 , 50 •].…”
Section: Challenges and Barriersmentioning
confidence: 94%
“…In this context, children with disabilities and their caregivers will be a subpopulation of particular importance, given DVAs' (future) potential to inform, assist, assess and support these individuals with special developmental or medical needs (Sezgin et al, 2020). Preliminary research already suggests commercial off-the-shelf DVAs are popular among individuals with disabilities (e.g., (Pradhan et al, 2018;Duffy et al, 2021)), but research is still limited, especially when focusing on concrete disabilities (e.g., (Cave & Bloch, 2021)). However, apart from general socio-economic and skill-related accessibility issues (Paul et al, 2021), children with different kinds of disabilities will experience different kinds of benefits and challenges.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%